PEMBELAJARAN BERBASIS PORTOFOLIO DALAM PENDIDIKAN IPS - Rahmat Mamuasi; Narilah A Tuara (Jurnal Pendidikan dan Ekonomi (JUPEK), 2021)
The results of the study show that portfolio-based learning in social studies is learning developed from constructivist learning theory which emphasizes more on student activities during the learning process. this lesson too able to bring out students' ability to work together, the ability to solve problems in groups, raise students' courage in ask, answer questions, and do the questions in front of the class. Basically the portfolio as a learning model is an effort made by the teacher so that students have the ability to express and express themselves as individuals or groups. This ability is obtained by students through learning experiences so that they have the ability to organize the information they find, make reports and write down what is on their minds, and then put it in full in their work / assignments. The portfolio learning model is always followed by a portfolio assessment model (portfolio evaluation). In principle, portfolio assessment is carried out continuously with an emphasis on assessing the entire document of learning outcomes by taking into account the self-evaluation carried out by students. This assessment is intended to measure students' abilities in the learning process and evaluate teacher performance in relation to the success or failure of the implementation of the portfolio learning process.